Parent Engagement in Students’s Learn from Home Activity - Fitriah, Fitriah; Arifin, Ahmad; Ibrahim, Faisol Mahmud Adam (Journal of Applied Transintegration Paradigm, 2022)
This study tells the role of parents who are Civil Servants in accompanying their children to study from home during the Covid-19 pandemic. This study method uses qualitative approach with the type of case study on parents who are Civil Servants in accompanying their children to study from home during the Covid-19 pandemic. The data were collected through semi-structured interview, observation and documentation are related to the role of parents in accompanying their children to learn from home. Then the data were analyzed by thematic analysis techniques. The study shows that the role of parents who are Civil Servants in accompanying their children to study from home during the Covid-19 pandemic is to act as teachers at home, as facilitators by providing various facilities such as learning that is relevant to the Covid-19 pandemic situation, and as a motivator.